2022
DOI: 10.31234/osf.io/fz6aw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rose-colored glasses or suspicion? Effects of coalitional cues on evaluations of checks and balances reforms

Abstract: Why do citizens (re-)elect leaders and parties that systematically undermine democratic institutions? Democratic backsliding is a process in which political leaders with authoritarian tendencies alter democratic checks and balances. Reforms of checks and balances can reshape and undermine existing democratic institutions and skew the political playing field in the advantage of authoritarian incumbents and their supporters. How do citizens respond to such reforms? In this article I study the effects of coalitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These hypotheses capture the possible effects of different factors, but they leave out one of the most prominent proposed explanations of citizen attitudes towards aspects of democracy -partisanship and party cues. There is a large number of studies suggesting that support for democratic principles is strongly affected by the parties favoured by the citizens and the messages these parties send (Carey et al 2022;Fossati, Muhtadi, and Warburton 2021;Frederiksen 2024;Gidengil, Stolle, and Bergeron-Boutin 2022;Graham and Svolik 2020;Mazepus 2022;Simonovits, McCoy, and Littvay 2022;Touchton, Klofstad, and Uscinski 2023). We do not disagree with these results and accept that partisanship likely plays a big role in whether people will be accepting of policy decisions that ignore social protests or not, e.g.…”
Section: Policy Salience and Interaction Effectsmentioning
confidence: 62%
“…These hypotheses capture the possible effects of different factors, but they leave out one of the most prominent proposed explanations of citizen attitudes towards aspects of democracy -partisanship and party cues. There is a large number of studies suggesting that support for democratic principles is strongly affected by the parties favoured by the citizens and the messages these parties send (Carey et al 2022;Fossati, Muhtadi, and Warburton 2021;Frederiksen 2024;Gidengil, Stolle, and Bergeron-Boutin 2022;Graham and Svolik 2020;Mazepus 2022;Simonovits, McCoy, and Littvay 2022;Touchton, Klofstad, and Uscinski 2023). We do not disagree with these results and accept that partisanship likely plays a big role in whether people will be accepting of policy decisions that ignore social protests or not, e.g.…”
Section: Policy Salience and Interaction Effectsmentioning
confidence: 62%
“…A pilot survey experiment conducted with a representative sample in Poland (Mazepus 2022) found that citizens were especially weary of attempts by politicians to limit the right to protest (in comparison to the extension of the presidential term limit and violations of the independence of judges). This finding indicates that there might be differences in the value assigned to different checks and balances that are a result of particular political intuitions.…”
Section: Wp3: Consequences For Democracies: Intuitions and The Trade-...mentioning
confidence: 99%